Analysis of the Influence of Leadership Style on Employee Work Discipline at the Medan Tourism Academy - Arnedi, Arnedi (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
Basically, a leader must have capabilities to influence his subordinates to follow him and to be in accordance with the vision of the organization that has been stated. The implementation of good leadership styles may give positive contribution to the increase of employees’ work discipline. The good or bad leadership styles of a leader would affect the good or bad work discipline of employees who work under him. This study focuses on the problem of how leadership styles will affect work discipline of employees in Medan tourism academy. The purposes of the study are : 1) to determine and to analyse the impact of leadership styles on work discipline of employees in Medan tourism academy, 2) to determine and to analyse dominant variables which affect work discipline of employees in Akademi Pariwisata Medan. The hypothesis of the study is leadership styles affect work discipline of employees in Akademi Pariwisata Medan. There were 99 employees of Medan tourism academy considered as population. Using the Slovin formula, 50 samples were taken which were based upon the proportion of unit strata. The primary data were obtained through interviews and questionnaires, meanwhile the secondary data were obtained through the studies of documentation in the forms of official documents issued by Akademi Pariwisata Medan. The method of data analysis was descriptive statistical analysis using multiple linear regression. The results of the study showed that simultaneously the leadership styles (authoritarian, participatory, delegative) affect work discipline of employees in Medan tourism academy. The partial test showed that participatory style of leadership was significantly dominant influential on work discipline of employees in Medan tourism academy, followed by delegative style of leadership. However, authoritarian style of leadership was not significantly influential on work discipline of employees, in accordance with test results of coefficient value t count < t table.